A Portrait Of Minang Migrant Women At Parung Panjang West Java - Ningsih, Wirda (AGENDA: Jurnal Analisis Gender dan Agama, 2022)
Most of Minang Women become a trader or seller at Parung Panjang Market, West Java. Regarding to this phenomenon, there are some questions raised like the reasons of selecting career as seller or trader, the relation between social structure of Minang culture in comprehending the market, and the connection between economic behavior of Minang people with the market. Therefore, this research is worth it to be conducted through field research with qualitative approach. Data were collected by observation, interview, and documents. The interview was done to some market players and Minangkabau culture experts. Meanwile, documents are used to elaborate social structure of Minang culture. There are two implications in this research; first, there is a correlation between Minang nomad women in comprehending the market at Paruh Panjang, and second, there is a relationship between social culture systems with economic behavior in gaining success.